DAMPAK PEMBUANGAN SAMPAH TERHADAP AKTIVITAS EKONOMI MASYARAKAT DI REKLAMASI PESISIR PANTAI KOTA TERNATE PROPINSI MALUKU UTARA - Drakel, Anhar (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
This research aims to determine the environmental impact of coastal reclamation on the economic activities of communities on the coast of Ternate City, North Maluku Province. This research uses a quantitative approach research method, the subjects of this research are people who sell in the market around the coastal reclamation of Ternate City. The data used in this research are (1) primary data, using questionnaires. The data collection methods used in this research are observation, interviews, questionnaires (2) secondary data was obtained using the library/literature study method. The sample consisted of 25 people using random sampling, for data collection techniques through interviews, observation and documentation. The data analysis technique used in this research is multiple regression analysis using SPSS 18 using multiple regression equations. The research results show that the level of education together has a positive and significant effect on income, environmental knowledge and environmental socialization. This can be seen from the regression coefficient of 0.020 and standard error of 0.47. The null hypothesis is rejected with p. value of 0.003 which is smaller than 0.05.